2021
DOI: 10.1002/anie.202114551
|View full text |Cite
|
Sign up to set email alerts
|

Transformation Pathways in Colloidal CdTeSe Magic‐Size Clusters

Abstract: Ararely studied transformation in colloidal ternary magic-size clusters (MSCs) is addressed. We report the first observation of the transformation from ternary CdTeSe MSC-399 to MSC-422, whichoccurs at room temperature.These two MSC types displaysharp optical absorption resonances at 399 and 422 nm, respectively,and are related in that they are quasi isomers,together with their counterpart precursor compounds (PCs). Binary CdTea nd CdSe samples were prepared in the prenucleation stage also called the induction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 55 publications
2
30
0
Order By: Relevance
“…In addition to the present CE reaction, we have demonstrated that the binary ME PC can experience another four chemical reactions. They are isomerization to binary ME MSCs, , ,,, substitution reactions followed by isomerization to binary or ternary MSCs (Figure S1B), , ,, addition reactions followed by isomerization to photoluminescent MSCs (Figure S1B), and fragmentation to QDs. , For the reaction of M and E precursors to ME QDs, the E precursor dominates the self-assembly of the M and E precursors that results in the formation of the ME PC with similar stoichiometry. The present finding of the E-dominated, magic self-assembly principle, together with the recent discovery of these binary and ternary MSCs and the successful synthesis of small-size QDs with enhanced yield, demonstrates that we are able to push further “chemical self-assembly” …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the present CE reaction, we have demonstrated that the binary ME PC can experience another four chemical reactions. They are isomerization to binary ME MSCs, , ,,, substitution reactions followed by isomerization to binary or ternary MSCs (Figure S1B), , ,, addition reactions followed by isomerization to photoluminescent MSCs (Figure S1B), and fragmentation to QDs. , For the reaction of M and E precursors to ME QDs, the E precursor dominates the self-assembly of the M and E precursors that results in the formation of the ME PC with similar stoichiometry. The present finding of the E-dominated, magic self-assembly principle, together with the recent discovery of these binary and ternary MSCs and the successful synthesis of small-size QDs with enhanced yield, demonstrates that we are able to push further “chemical self-assembly” …”
Section: Discussionmentioning
confidence: 99%
“…In addition to the present CE reaction, we have demonstrated that the binary ME PC can experience another four chemical reactions. They are isomerization to binary ME MSCs, [2][3][4][5][14][15][16]18,34,35 substitution reactions followed by isomerization to binary or ternary MSCs (Figure S1B), 17,[34][35][36][37]53,54 addition reactions followed by isomerization to photoluminescent MSCs (Figure S1B), 55 and fragmentation to QDs. 2,56 For the reaction of M and E precursors to ME QDs, the E precursor dominates the selfassembly of the M and E precursors that results in the formation of the ME PC with similar stoichiometry.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…When colloidal II-VI semiconductor magic-size clusters (MSCs) transform in a reaction from one type to another, the redshift pattern of optical absorption is generally accepted to be step-wise and not continuous. [1][2][3][4][5][6][7][8] A continuous redshift behavior, on the other hand, is normally expected for semiconductor quantum dots (QDs) from the growth in their size. [9][10][11][12] For the lowest energy transition of a MSC, the absorption peak is relatively narrow and the peak position usually occurs at a constant wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…Table S1 summarizes the acronyms used in the present study. In mixtures of binary CdTe and CdSe IP samples, we demonstrated the first evolution of ternary CdTeSe MSC-399 that exhibits sharp optical absorption peaking at the wavelength of 399 nm. For our room-temperature approach, the two binary samples were separately prepared at relatively high temperatures. Then, they were mixed at room temperature; CdTeSe MSC-399 developed during the room-temperature incubation of the resultant mixture.…”
mentioning
confidence: 96%
“…Colloidal II–VI metal (M) and chalcogenide (E) semiconductor magic-size clusters (MSCs) have their own special precursor compounds (PCs). While MSCs display sharp optical absorption at constant wavelengths, their counterpart PCs are transparent at these and longer wavelengths. The idea that MSCs evolve from their corresponding PCs via intramolecular reorganization is present in the two-pathway model that provides an in-depth understanding of the growth relation between binary ME MSCs and binary colloidal semiconductor ME quantum dots (QDs) (Scheme S1a).…”
mentioning
confidence: 99%